EFEKTIVITAS ANGGARAN PENDAPATAN DAN REALISASI ANGGARAN (APBDES) DESA PERSATUAN PULAU RAKYAT TUA KABUPATEN ASAHAN - Sri Ayu Purnama Ningsih; Nur Fadhilah Ahmad Hasibuan (UNIVERSITAS DHARMAWANGSA, 2022)
This study aims to determine the level of effectiveness of the use of the revenue budget and budget realization (APBDes) in the unitary island village of the old people, Asahan district. This research uses descriptive quantitative research with secondary data type. Where data can be measured or calculated directly in the form of information or explanation expressed in numbers or in the form of numbers. Using reduction research techniques, interviews and documentation. Based on the results of the study, it can be concluded that the effectiveness of the revenue budget in Unity Pulau Rakyat Tua Village, Asahan Regency from 2019 to 2021 has reached the target and the percentage can be said to be overall good. in 2019-2021 the expenditure realization funds have not reached the set spending targets so that the criteria are said to be ineffective, said to be ineffective because of the lack of achievement in the spending targets that have been set in the Pulau Rakyat Tua Unity Village, Asahan Regency.